Effects of a question prompt sheet on active patient behaviour: A randomized controlled trial with depressed outpatients. (May 2014) - Hamann, Johannes; Maris, Nikolaos; Iosifidou, Paraskevi; Mendel, Rosmarie; Cohen, Rudolf; Wolf, Petra; Kissling, Werner
Background: A deeper engagement into medical decision-making is demanded by treatment guidelines for patients with affective disorders. There is to date little evidence on what facilitates active behaviour of patients with depression. In general medicine 'question prompt sheets' (QPSs) have been shown to change patients' behaviour in the consultation and improve treatment satisfaction but there is no evidence for such interventions for mental health settings. Aims: To study the effects of a QPS on active patient behaviour in the consultation. Methods: Randomized controlled trial (involving N = 100 outpatients with depression) evaluating the effects of a QPS on patients' behaviour in the consultation. Results: The QPS showed no influence on the number of topics raised by patients ( p = .13) nor on the external rater's perception of 'Who made the decisions in today's consultation?' ( p = .50). Conclusions: A QPS did not change depressed patients' behaviour in the consultation. More complex interventions might be needed to change depressed patients' behaviour within an established doctor–patient dyad. Patient seminars addressing behavioural aspects have been shown to be effective in other settings and may also be feasible for outpatients with affective disorders.